The Importance of Green Education in Indonesia: An analysis of Opportunities and Challenges - Adnyana, I Made Dwi Mertha; Mahendra, Kadek Adi; Syed Meesam Raza (Education Specialist, 2023)
This study aimed to explore the importance of green education in Indonesia by investigating the opportunities and challenges that arise from a literature review. Learner constructivism emphasizes students’ active involvement in exploring environmental concepts, whereas critical thinking enables them to analyze, synthesize, and evaluate information to make sound judgments. There are several opportunities to implement green education in Indonesia, particularly to address environmental challenges, promote sustainability, and foster the generation of environmentally conscious individuals. However, there are challenges to implementing green education, such as limited resources, insufficient teacher training, and resistance to change. In the future, green education should be integrated into educational curricula and programs to foster environmental awareness, promote sustainable practices, cultivate critical thinking skills among learners, and minimize actions that harm the environment.